Upaya Peningkatan Motivasi Kerja Dalam Membentuk Kinerja Pegawai Dinas Sosial Kota Surakarta Di Masa Pandemi Covid-19 - Agung Prihanto; I Gusti Putu Diva Awatara (STIE AUB Surakarta, 2022)
This study aims to analyze and provide empirical evidence of the effect of competence, work from home and organizational commitment on work motivation as well as the influence of competence, work from home, organizational commitment and motivation on the performance of Surakarta City Social Service employeesThis research was conducted at the Surakarta City Social Service. The population used in this study amounted to 37 State Civil Apparatuses at the Surakarta City Social Service. The sample used in this study was 37 state civil servants using a census sampling technique. Data collection techniques used were questionnaires and interviews. The data analysis technique used is the research instrument test using validity and reliability tests; linearity test; path analysis; hypothesis testing using the t test, F test and analysis of the coefficient of determination (R2).The results of the study show that competence has a negative and insignificant effect on work motivation; work from home has a positive and insignificant effect on work motivation; Organizational commitment has a negative and insignificant effect on employee motivation. Competence has a positive and insignificant effect on employee performance; work from home has a negative and significant effect on employee performance; organizational commitment has a positive and significant effect on employee performance; work motivation has a positive and significant effect on the performance of Surakarta City Social Service employees; the results of the F test on the second equation can be concluded that together commitment, work from home, organizational commitment and motivation have a significant effect on the performance of Surakarta City Social Service employees. The total R2 value of 0.559 means that the performance of social service employees in the city of Surakarta is explained by competence, work from home, organizational commitment of 55.9%, the remaining 44.1% is explained by other variables outside the research model, for example variables of compensation, communication, work environment, culture organization and leadership